Removal of PO43- and Cu2+ Using Ferrihidrit-Chelex 100 Gel by Adsorption Coloumn - Risma Putri Disicahyani; Barlah Rumhayati; Atikah Atikah (The Journal of Pure and Applied Chemistry Research, 2014)
In the drinking water, there is a heavy metals and nutrient that is harmful to human health, such as phosphate and Cu2+ by product or waste material from sewage population, industry and agricultural. Government Regulation Number 82 at 2001 has said 0.2 mg PO43-/L and 2 mg Cu/L for maximum concentration in the drinking water. Resins chelex 100 and ferrihydrite could be used as a adsorbent for adsorption PO43- and Cu2+. Active sites of adsorbent chelex 100 was used as cation exchanger  because of its  negatively charged (-CH2COO-),  while ferrihydrite was used as anion exchanger  because of its positively charged (OH2+). Removal of Cu2+ are based on the formation of chelate compunds between iminodiacetic functional group and Cu2+, while ferrihydrite and PO43- was through the electrostatic interactions. Composition of ferrihydrite-chelex 100 used was 1:1. In this composition, could be removed PO43- and Cu2+ optimally at volume 7.5 mL with percentage of analyte were 97.66 % PO43- and 96.33% Cu2+. High desorption percentage of PO43- and Cu2+ could be achieved at 86.61% and 60.87% when H2SO4 0.3 M used. In the drinking water, ferrihydrite-chelex 100 gel could removed PO43- and Cu2+ from the refills water with removal percentage between 71 and 81% while from a tap water 84-98% at pH 5, respectivelly.